MOTIVATION AND SELF-LEARNING READINESS OF BLENDED LEARNING IN RESEARCH AND STATISTICS COURSE FOR UNDERGRADUATE NURSING STUDENTS - Eka, Ni Gusti Ayu; Houghty, Grace Solely; Juniarta, Juniarta (JOHME: Journal of Holistic Mathematics Education, 2019)
Though blended learning has been applied in nursing schools in Indonesia, the number of studies with regards to students’ motivation and self-readiness in their courses is still lacking. In addition, many student nurses claimed that the Research and Statistics course was more difficult than other nursing courses. This study aimed to assess the nursing students’ motivation and self-learning readiness of blended learning in a Research and Statistics course of the Faculty of Nursing at Universitas Pelita Harapan. The preliminary study recruited forty nursing students for validity and reliability test purposes. Two questionnaires were translated and tested including the adapted Academic Motivation Scale and the adapted Self-Directed Learning Readiness Scale for Nursing Education. Both Cronbach’s alphas of the questionnaires were above 0.8 (good reliability), however some questions were revised based on its validity test results and its readability. A total of 181 students were involved in the study and descriptive statistics were applied in the data analysis. The findings showed that nursing students had relatively moderate self-directed learning readiness (mean 90.18). With regards to academic motivation, students’ intrinsic motivation to know (mean 3.35) was higher than in other subdimensions of academic motivation. It also means that most of the students felt happy while learning and exploring something new in the course. In conclusion, motivation and self-learning readiness of students are important when applied to a blended course. It is recommended that nurse educators should identify students’ motivation and self-learning readiness to provide student-centered learning especially in a Research and Statistics course. Further research may involve more universities in different regions of Indonesia.BAHASA INDONESIA ABSTRAK: Meskipun blended learning telah diterapkan di pendidikan keperawatan di Indonesia, sejumlah studi berkaitan dengan motivasi dan kesiapan diri mahasiswa dalam pembelajaran mereka masih kurang. Selain itu, banyak mahasiswa perawat mengklaim bahwa mata kuliah Penelitian dan Statistik lebih sulit daripada mata kuliah keperawatan lainnya. Penelitian ini bertujuan untuk mengidentifikasi motivasi mahasiswa keperawatan dan kesiapan belajar sendiri dalam mata kuliah Penelitian dan Statistik dengan blended learning di Fakultas Keperawatan Universitas Pelita Harapan. Studi pendahuluan merekrut empat puluh mahasiswa keperawatan untuk keperluan uji validitas dan reliabilitas. Dua kuesioner diterjemahkan dan diuji yaitu Skala Motivasi Akademik dan Skala Kesiapan Belajar Sendiri (self-directed readiness) yang telah disesuaikan untuk pendidikan keperawatan. Hasil uji kedua kuesioner mempunyai nilai Cronbach Alpha berada di atas 0,8 (reliabilitas yang baik), namun beberapa pertanyaan direvisi berdasarkan pada hasil tes validitas dan keterbacaannya. Sebanyak 181 siswa terlibat dalam penelitian ini dan statistik deskriptif diterapkan dalam analisis data. Dalam penelitian ini, terungkap bahwa mahasiswa keperawatan memiliki kesiapan belajar mandiri yang relatif sedang (rata-rata 90,18). Sehubungan dengan motivasi akademik, motivasi intrinsik mahasiswa untuk mengetahui (rata-rata 3,35) lebih tinggi daripada sub-dimensi lain dari motivasi akademik. Ini juga berarti bahwa sebagian besar mahasiswa merasa bahagia saat belajar dan menggali sesuatu yang baru dalam pembelajaran. Sebagai kesimpulan, motivasi dan kesiapan diri adalah penting saat melaksanakan blended learning. Penelitian ini merekomendasikan agar pendidik perawat atau dosen untuk mengidentifikasi motivasi dan kesiapan diri mahasiswa dalam memberikan pembelajaran yang berpusat pada mahasiswa terutama dalam mata kuliah Penelitian dan Statistik. Penelitian selanjutnnya dapat memasukkan lebih dari satu universitas di daerah yang berbeda di Indonesia.